Belalai gajah (clinacanthus nutans) scientific evidence of cancer prevention - Hazrulrizawati, Hamid; Izzah Hayati, Yahaya; Roziasyahira, Mutazah (Penerbit UMP, 2020)
This book contains information about the traditional used and phytochemicals of belalai gajah (Clinacanthus nutans). This report had scientifically supported the testimonies of Malaysian who claimed that C. nutans possesses antitumor effects and had saved many of various cancer patients. The uses of plant in traditional medicine and current studies had been discussed. Single compounds had been isolated by purification using chromatographic techniques. Apart from that, a brief review of concept between chemical composition and biological activities also described in this book.